2021
DOI: 10.1556/030.2021.01487
|View full text |Cite
|
Sign up to set email alerts
|

Association between biofilm-production and antibiotic resistance in Escherichia coli isolates: A laboratory-based case study and a literature review

Abstract: Bacteria can enhance their survival by attaching to inanimate surfaces or tissues, and presenting as multicellular communities encased in a protective extracellular matrix called biofilm. There has been pronounced interest in assessing the relationship between the antibiotic resistant phenotype and biofilm-production in clinically-relevant pathogens. The aim of the present paper was to provide additional experimental results on the topic, testing the biofilm-forming capacity of Escherichia coli isolates using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 91 publications
0
16
0
2
Order By: Relevance
“…The emergence of P. aeruginosa isolates with different biofilm-forming capacities may also inform the genetic heterogeneity within these species, which is an important factor for successful infection in humans [9]. Nevertheless, differences in the phenotypes and susceptibility trends in these isolates may also stem from their different geographical origin and the sampling frame used [100]. The main limitation of our study was the reliance on the use of phenotypic methods only during the assessment of the resistance, biofilm-forming, and virulence phenotype of the isolates; therefore, we did not have data from molecular methods or on the clonal complexes (CCs) for the isolates implicated in the assays.…”
Section: Discussion Review Of the Literaturementioning
confidence: 99%
“…The emergence of P. aeruginosa isolates with different biofilm-forming capacities may also inform the genetic heterogeneity within these species, which is an important factor for successful infection in humans [9]. Nevertheless, differences in the phenotypes and susceptibility trends in these isolates may also stem from their different geographical origin and the sampling frame used [100]. The main limitation of our study was the reliance on the use of phenotypic methods only during the assessment of the resistance, biofilm-forming, and virulence phenotype of the isolates; therefore, we did not have data from molecular methods or on the clonal complexes (CCs) for the isolates implicated in the assays.…”
Section: Discussion Review Of the Literaturementioning
confidence: 99%
“…A biofilm is a complex matrix composed of polysaccharides, nucleic acids, proteins, lipids, water, various ions, and other organic components in which cells bind together to survive harsh conditions such as host defense and accumulation of various noxious substances and antimicrobial agents [ 38 ]. According to the recent assessment by the National Institute of Health (NIH), more than 60% of in vivo infections are due to biofilm-forming microorganisms [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several pathogens such as Enterococcus faecium , Staphylococcus aureus , Klebsiella pneumoniae , Acinetobacter baumannii , Pseudomonas aeruginosa , and Enterobacter spp. that are known as “ESKAPE” infections are distinguished by their strong biofilm formation [ 38 ]. Thus, the search for new antimicrobials with biofilm inhibition properties is urgently needed.…”
Section: Discussionmentioning
confidence: 99%
“…The inoculated microtiter plate was incubated for 24 h at 37 °C, and the adherent cells washed three times using a saline solution, and thereafter stained with a 0.1% crystal violet solution (Mikrochem, Pezinok, Slovakia). The adhering dye taken up by the adherent cells was dissolved by 30% acetic acid, and the optical In addition to rising antibiotic resistance amongst UPEC strains, the production of biofilms among these strains is another concern, often leading to recurrent UTIs and chronic infections [6]. Biofilm production has been shown to be an important UPEC virulence factor, as its formation creates an impermeable barrier for antibiotic penetration, and hence minimizing the amount of antibiotic that can reach the site of action, thus contributing to the development of resistance [7].…”
Section: Detection Of Biofilm Formationmentioning
confidence: 99%
“…Management of uncomplicated UTI has become challenging due to rise in antibiotic resistance among UPEC strains, including to traditional first-line agents, such as trimethoprimsulfamethoxazole (TMP-SMZ) [4]. Although the mechanisms of antibiotic resistance are diverse, previous studies have demonstrated that there is a potential link between antibiotic resistance and biofilm production [5], although other findings are to the contrary [6]. • Page 2 of 10 • underlying host conditions.…”
Section: Introductionmentioning
confidence: 99%